2008
DOI: 10.1016/j.jacc.2007.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Late Outcomes of Unprotected Left Main Stenting in Comparison With Surgical Revascularization

Abstract: Patients with ULMCA disease treated with PCI had favorable early outcomes in comparison with the CABG group. At 1 year, LVEF had improved significantly only in the PCI group. After more than 2 years, MACCE-free survival was similar in both groups with a trend toward improved survival after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
236
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(265 citation statements)
references
References 33 publications
8
236
2
8
Order By: Relevance
“…[147][148][149] Several studies comparing CABG to PCI, however, indicated that the advantage of CABG consists primarily of fewer repeat revascularizations. 139,[149][150][151][152][153][154][155] The study by Brener et al 156 indicates no significant mortality difference between PCI and CABG after 3 years of follow-up. Longer-term follow-up is needed.…”
Section: Recommendations For Pci For Unprotected Left Main Coronary Amentioning
confidence: 99%
“…[147][148][149] Several studies comparing CABG to PCI, however, indicated that the advantage of CABG consists primarily of fewer repeat revascularizations. 139,[149][150][151][152][153][154][155] The study by Brener et al 156 indicates no significant mortality difference between PCI and CABG after 3 years of follow-up. Longer-term follow-up is needed.…”
Section: Recommendations For Pci For Unprotected Left Main Coronary Amentioning
confidence: 99%
“…Despite equivalent survival, this more tenuous postoperative course is concerning, and therefore in accordance with these results, our current practice is to preferentially perform preoperative PCI with bare metal stents if technically feasible (exceptions may include left main disease and inability to tolerate antiplatelet therapy). The current guidelines by American College of Cardiology Foundation and the American Heart Association provide a Class 1 recommendation for CABG to improve survival in patients with significance stenosis of the left main coronary artery; however, they do note that PCI may be a reasonable alternative in selected patients (28 (29). In a randomized trial comparing CABG versus PCI for 1800 patients (SYNTAX trial NCT00114972), a prespecified subgroup analysis of 705 patients with left main disease demonstrated comparable safety and efficacy at 1 year; however, the authors noted the need for longer follow-up to confirm these findings (30).…”
Section: Discussionmentioning
confidence: 99%
“…Study 5 was conducted to determine the safety and efficacy of PCI compared to CABG in LM patients. A total of 105 patients who present with >50% LM coronary artery (LMCA) narrowing, with or without multivessel CAD, were randomized to either PCI (n=52) or CABG (n=53) to compare the early and late results of PCI and surgical revascularization of LMCA.…”
Section: Lm and Bifurcation Management: Outcomes Between Coronary Artmentioning
confidence: 99%
“…56 The optimal MSA cutoff that best predicted angiographic in-stent restenosis (ISR) after SES implantation on a segmental basis was 5 Figure 4.…”
Section: Incomplete Crush Distal Proximalmentioning
confidence: 99%